The Multilayered Migration Regime in Turkey: Contested Regionalization, Deceleration and Legal Precarization - Genc, Firat; Heck, Gerda; Hess, Sabine (Routledge Journals, Taylor & Francis Ltd, 2019)
Against the background of the research project on De-and Restabilizations of the European Border Regime, analyzing the recent political attempts by the EU and its member states to regain control over its borders and the movements of migration after the so-called European refugee crisis in 2015, this article discusses Turkey's role and position within international migration flows and the EU-driven border regime. Reflecting on the recent history of Turkey's migration and border politics, we argue that academic accounts, which tend to reduce Turkey's role to a simple extension of the EU border regime, are insufficient to explain the current state of affairs in Turkey. Rather, the article sheds light on the contested and multilayered nature of the Turkish migration regime, which can be partly read as reactions to the European Union, but also as an effect of its own foreign and national policy interests. The outcome is a highly hybrid political formation causing ambiguous legal, social, and political limitations for migrants and refugees, reflected in their journeys and in social and political realities, which are discussed as exemplified in the migratory stories of two migrants.
Keywords: Irregular Migration